2018
DOI: 10.11622/smedj.2018021
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of Singapore schoolchildren learning cardiopulmonary resuscitation and automated external defibrillator skills

et al.

Abstract: Introduction: Victims of out-of-hospital cardiac arrests require timely cardiopulmonary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…Improving secondary school student’s knowledge and attitudes towards performing CPR and using an AED is just as important as teaching the physical skills associated with the delivery of life-saving CPR and AED interventions. 19 The large gain in BLS knowledge (38%, 95% CI 33% to 43%) in this study appeared to be greater than the results comparing a baseline control group and three postinstructional methods (computer training, computer training plus practice, video plus demonstration and practice) for teaching CPR and AED. 20 Knowledge deficits in rate and depth of CPR compression were apparent before training in this study, but substantially improved and were retained at the 3-month follow-up.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…Improving secondary school student’s knowledge and attitudes towards performing CPR and using an AED is just as important as teaching the physical skills associated with the delivery of life-saving CPR and AED interventions. 19 The large gain in BLS knowledge (38%, 95% CI 33% to 43%) in this study appeared to be greater than the results comparing a baseline control group and three postinstructional methods (computer training, computer training plus practice, video plus demonstration and practice) for teaching CPR and AED. 20 Knowledge deficits in rate and depth of CPR compression were apparent before training in this study, but substantially improved and were retained at the 3-month follow-up.…”
Section: Discussioncontrasting
confidence: 61%
“…BLS instructors reassuring students, for example, about the trade-off of a victim with CPR-related broken ribs having a higher chance of survival versus poorer outcomes without CPR could partly address this common misconception. 19 Nearly half of our students were worried about the legal responsibility in performing CPR as a Good Samaritan Law is not in place. A local survey showed that if the Good Samaritan Law was enacted, 57% of first aid course participants indicated they would be more willing to perform bystander CPR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations